Moore's Law and the Sand-Heap Paradox. - Vardi, Moshe Y. (Communications of the ACM, 2014)
The article focuses on the end of Moore's Law and how it may impact the economy and software development. It states computer performance isn't automatically improved by increased transistor density, and suggests Moore's Law is about both improved performance and improved cost-performance. It talks about complementary metal oxide semiconductors (CMOS) and claims increases in CMOS capacity will be accompanied by reduced performance and reliability. It mentions opportunities for computing research.